2020
DOI: 10.1016/j.redox.2020.101691
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated cofilin-2 is more prone to oxidative modifications on Cys39 and favors amyloid fibril formation

Abstract: Cofilins are small protein of the actin depolymerizing family. Actin polymerization/depolymerization is central to a number of critical cellular physiological tasks making cofilin a key protein for several physiological functions of the cell. Cofilin activity is mainly regulated by phosphorylation on serine residue 3 making this post-translational modification key to the regulation of myofilament integrity. In fact, in this form, the protein segregates in myocardial aggregates in human idiopathic dilated cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
(113 reference statements)
0
11
1
Order By: Relevance
“…In the last two decades, smectites and, in general, clay minerals were employed as substrates for different and various fundamental and applied research involving biomolecules. For example, clays are able to condense, organize, and concentrate biomolecules of different kinds and sizes [15][16][17][18][19][20][21], and, if the clay substrates present both Brønsted and Lewis acid sites [22,23], they may also act as catalysts. Notwithstanding the important biotechnological applications of clay minerals, these types of studies are also of utmost interest in the field of prebiotic chemistry, i.e., in all the steps (selection, concentration, synthesis, and protection) that lead from the basic building blocks of life (amino acids, nucleotides, lipids) to functional macromolecules (peptides, RNA/DNA, membranes) and, eventually, to the first cell [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, smectites and, in general, clay minerals were employed as substrates for different and various fundamental and applied research involving biomolecules. For example, clays are able to condense, organize, and concentrate biomolecules of different kinds and sizes [15][16][17][18][19][20][21], and, if the clay substrates present both Brønsted and Lewis acid sites [22,23], they may also act as catalysts. Notwithstanding the important biotechnological applications of clay minerals, these types of studies are also of utmost interest in the field of prebiotic chemistry, i.e., in all the steps (selection, concentration, synthesis, and protection) that lead from the basic building blocks of life (amino acids, nucleotides, lipids) to functional macromolecules (peptides, RNA/DNA, membranes) and, eventually, to the first cell [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The available literature suggests that cofilin-2, the muscle isoform of the ADF/cofilin family, is involved in the etiology of various pathological conditions, such as protein aggregate accumulations in cardiomyopathies [17]. Pignataro et al suggested that the phosphorylated cofilin-2 might form amyloid-like fibrillar structures, but only under pathophysiological conditions, such as oxidative distress [4]. However, the cofilin-2 amyloid formation under physiological conditions remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that phosphorylation of cofilin-2 promotes its aggregation under oxidative distress [4]. We asked whether the protein stability is affected by the phosphorylation of cofilin-2.…”
Section: Phosphorylation Did Not Significantly Affect Cofilin-2 Stabilitymentioning
confidence: 98%
See 2 more Smart Citations